Investigation of Magnetic and Optical Properties of Mn-Doped SnO2 at Different Annealing Temperatures - Negi, S.; Sharma, A.; Sharma, P. (Journal of Scientific Research, 2020)
In this paper, a systematic investigation has been done to study the effect of variation in annealing temperature on magnetic and optical properties of Mn-doped SnO2. Co-precipitation technique has been used to synthesize Sn1-xMnxO2 samples with low Mn concentration (2 %). Pristine SnO2 is sintered at 350 oC. Mn-doped SnO2 samples are sintered at 350, 450, 550 and 650 oC. The structures of tetragonal rutile of SnO2 and Mn-doped SnO2 have been confirmed by the XRD pattern. Typical ferromagnetic ordering has been observed for Mn-doped SnO2 samples annealed at different temperatures. However, on increasing the annealing temperature saturation magnetization as well as the coercive field decreases, indicating a crucial phase transformation from ferromagnetism to paramagnetism. UV-Vis spectroscopy shows increase in absorbance and a slight shift in the absorption edge with Mn-doping at increasing annealing temperature indicating shifting of absorption peak towards higher wavelength. Tauc’s plot has been used to find the optical band gap (Eg).